The great pretender [compact disc, unabridged] : the undercover mission that changed our understanding of madness - Cahalan, Susannah (Hachette Audio, Grand Central Pub., 2019)
In 2009, 24-year-old Susannah Cahalan hovered on the precipice between life and death. Even as her doctors informed her family that she had incurable schizophrenia and would spend the rest of her short life in an institution, another doctor down the hall performed one final, informal test that, miraculously, delivered a lifesaving diagnosis: her disease was brought on by a physical problem and therefore treatable, more 'real,' in other words, than the intangible problem of a purely mental illness. Susannah is the rare patient who has experienced both sides of this divide: the compassionate response to a treatable, physical diagnosis and the frightening realities of the label of insanity.